Implementation of Sotoy (Student Organization Talking of Yellow Book) in Understanding Classical Arabic Books Using English at Darussalam Islamic Boarding School - Fahim Hilmy Ahimsa, Ahmad; Zumala Dwi Andriani , Zulfi (Darussalam English Journal (DEJ), 2024)
Abstract These books contain basic Islamic teachings that serve as a guide for students in understanding aqidah, fiqh, and morals. However, challenges arise when students need to understand and convey their knowledge in a broader context, where English language skills become increasingly necessary. Learning the yellow book in Islamic boarding schools is a long-standing tradition, especially among traditional Islamic boarding schools in Indonesia. The yellow book contains classical Islamic religious texts in Arabic that teach various Islamic disciplines, from interpretation, fiqh, hadith, to tasawuf. This tradition has become a main pillar in the formation of the character of students who not only have a deep understanding of Islamic teachings, but also skills in reading, understanding, and interpreting classical religious texts. This study uses a qualitative approach with a case study design to explore the experiences of students in the Yellow Book Discussion student organization program at the Darussalam Islamic Boarding School. Data collection was carried out through in-depth interviews, participant observation, and documentation related to the program, such as curriculum and teaching materials. The validity of the findings was guaranteed through triangulation and member checking, while ethical principles were adhered to by obtaining permission from the Islamic boarding school and informed consent from participants. The results of this study indicate that the implementation of the yellow book discussion student organization in English at the Darussalam Islamic Boarding School provides significant benefits in improving students' understanding of classical Arabic books, as well as developing critical and analytical thinking skills. However, several challenges such as limited English language proficiency among students need attention to ensure the overall effectiveness of this program.